(3bWYI ef cJGH aj GdLHQs - (3eLghds
(3ChdgG (B:s
(3GdHGH GdKGef ef GdCHhGH GdYTQI cGFf aj HjGf GSJNQGL GdeLghdGJ HWQjb GdLHQ hGdebGHdI hajg aUdGf GYde Gf Yde GdLHQ hGdebGHdI Yde TQja haf dWja EP cKjQG eG JeS GdMGLI Edjg aj cKjQ ef CHhGH Gdabg s
(3BNQgG (B:s
(3hCeG eG Ydi SHjd GdJcejd aeKGdg YOO faU ef fUa eQHYg Hbi GKfG YTQ aGbQV GdeLghd TjFG heQHYg eGd hfUag fUa eGd aEPG fbUJ GTj ef fUa GdeGd Hbj fUa eGd Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdQjGVjGJs